UPAYA MENINGKATKAN HASIL BELAJAR MELALUI MEDIA LINGKUNGAN SEKOLAH ( MEDLINGSEK ) DAN METODE OBSERVASI BAGI SISWA KELAS IV SD.NEGERI 132409 KOMPETENSI SUMBER DAYA ALAM TAHUN PELAJARAN 2022/2023 - Ahmad Jais (JGK (Jurnal Guru Kita), 2023)
Efforts to Improve Learning Outcomes Through School Environment Media (Medlingsek) and Observation Methods for Grade IV SD Students. Country 132409 Competence in Natural Resources for the 2022/2023 Academic Year. This study aims to find out: 1) To find out whether the use of MEDLINGSEK (School Environmental Media) can improve student learning outcomes in science learning on natural resources material in class IV SD Negri 132409 Tanjung Balai City. 2) Identify problems that occur in the science teaching and learning process in class IV SD Negri 132409 Tanjungbalai City. The research subjects were Grade IV students of SD Negri 132409 Tanjungbalai City. Research location for grade IV State Elementary School - 132409 Jalan MT. Haryono. The research method uses Classroom Action Research (CAR). The results showed that the average student score during the Preliminary Test was 63.38% with learning completeness of 46.42%, but after the action was taken in cycle I, the average learning outcomes of 53.57% where 15 students or 64.63% of students have reached the level of mastery of learning (total score of 70). (total value 70). Thus, the use of the MEDLINGSEK (School Environment Media) observation method can increase students' reasoning to understand science lessons more easily and clearly because they are learned directly through seeing and experiencing directly by the students themselves.